Spatial-temporal distribution and impact factors of irrigation water use efficiency in the grain production of China - Guo, Xiangping; Wu, Mengyang; Cao, Xinchun; Wang, Zhenchang (International Journal of Agricultural and Biological Engineering, 2018)
The marginal water productivity (MWP) model for the real irrigation water use performance and productivity assessment, applies to the regional scale was established in this study. The temporal-spatial patterns and attribution analyses of the indicator were conducted using spatial autocorrelation and path analysis methods. The results showed that with an average annual increase of 3.4%, the national MWP was estimated to be 0.542 kg/m, between 1998 and 2010. The spatial autocorrelation analysis results showed the global Moran’s I inspection values (Z) were higher than the confidence level, and the provinces, municipalities and autonomous regions (PAMs) with similar MWP values showed significant aggregation. Regions with a high value are centered in the middle and lower streams of the Yellow River, and those regions with a lower MWP were distributed in northeastern China and south of the Yangtze River. The precipitation and temperature are the major meteorological factors that determined the indicator, while extending the fertilizer and agricultural machinery input is the effective approach for improving the regional MWP. The major grain producing areas of North and Northeast China should take measures to raise their MWP, ensure food security and the sustainable use of water resources. Keywords: water use efficiency, the marginal output, spatial autocorrelation, path analysis, food security DOI: 10.25165/j.ijabe.20181105.3588 Citation: Guo X P, Wu M Y, Cao X C, Wang Z C. Spatial-temporal distribution and impact factors of irrigation water use efficiency in the grain production of China. Int J Agric & Biol Eng, 2018; 11(5): 131–138.